Behind enemy lines - Davis, John.; Veloz, David; Penn, Zak, 1968-; Moore, John, 1970-; Wilson, Owen, 1968-; Hackman, Gene.; Macht, Gabriel, 1972-; Almeida, Joaquim de, 1957-; Keith, David, 1954-; Krupa, Olek.; Mashkov, Vladimir; Whitfield, Charles Malik; et al. ([United States] : 20th Century Fox Home Entertainment, 2002)
Navy flight navigator Lt. Burnett and his pilot are shot down over Bosnia during a routine reconaissance mission after seeing something the Serbian forces didn't want them to see. Once on the ground, deep inside enemy territory, the chase is on as they are tracked by rebel forces who want to make sure they are dead. Meanwhile back on the aircraft carrier, the commander, who wants to mount a rescue mission, must play political games to make it happen.
Originally produced as a motion picture in 2001.
Based on the story by James Thomas and John Thomas.
Special features: Commentary by director John Moore and editor Martin Smith; commentary by producers John Davis and Wick Godfrey; behind-the-scenes featurette; original "main title sequence" and "end title sequence" with optional commentary; alternate "Tale off" montage with optional commentary; 3 extended director's cut scenes.
Director of photography, Brendan Galvin ; editor, Paul Martin Smith ; music composer, Don Davis ; costume designer, George L. Little ; production designer, Nathan Crowley.
Owen Wilson, Gene Hackman, Gabriel Macht, Joaquim de Almeida, David Keith, Olek Krupa, Vladimir Mashkov, Charles Malik Whitfield.
MPAA rating: PG-13.
Keywords: United States. -- Navy -- Drama; Yugoslav War, 1991-1995 -- Drama; Video recordings; Feature films; Films for the hearing impaired; War films